PENERAPAN MEDIA PEMBELAJARAN VIDEO TUTORIAL TATA RIAS WAJAH SEHARI-HARI MENGGUNAKAN BAHASA ISYARAT PADA SISWA TUNA RUNGU DI SMALB-B KARYA MULIA SURABAYA - Alisa Sidqi Maulidia; Mutimmatul Faidah; Sri Dwiyanti; Dewi Lutfiati (Program Studi Pendidikan Tata Rias, 2025)
Video tutorial media can improve understanding, motivation, participation, and is flexible. This study aims to determine the effectiveness of applying video tutorial learning media for daily makeup based on sign language for deaf students. The research approach used is Research and Development (R&D) with a 4D model (Define, Design, Develop, Disseminate). Data collection methods include observation, learning outcome tests, and questionnaires. The research subjects were 8 deaf students in grades X, XI, and XII at SMALB-B Karya Mulia Surabaya who chose beauty as their focus, The data obtained were analyzed descriptively quantitatively to determine the feasibility of the media and its effectiveness in improving student learning outcomes. The results showed that based on the Validator's assessment, the media scored 4.6 with very feasible criteria. The achievement of student learning outcomes was 88%, indicating that the learning objectives were met, achieving mastery of deaf students' abilities in performing daily makeup. The average student response score was 4.54, which shows very feasible criteria. Therefore, the application of video tutorial learning media using sign language can be an effective alternative learning method for deaf students.